Thinking critically in the age of Artificial Intelligence: A correlational study with college students - Rubio Campos, Lucila Milagros; Guzmán Meza, Maritza Emperatriz; Rojas Castilla, Lily Abigail; Torres Caceres, Fatima Del Socorro; Castillo Valeriano, Maria Del Rosario; Anco Estrella, Elizabeth Victoria; Cheng Rivadeneira, Augusto Enrique (LACCEI, 2025)
Abstract-. The present study analyzes the relationship between attitudes towards artificial intelligence (AI) and critical thinking in university students of a University of Metropolitan Lima. Under a quantitative approach and correlational design, validated instruments were applied to a sample of 100 undergraduate students, including the scale of attitudes towards AI and a critical thinking questionnaire composed of two dimensions: analytical ability and argumentative ability. The results of Spearman’s analysis revealed weak and non-significant positive correlations between the variables: general critical thinking (ρ = 0.177; p = 0.078), analytical ability (ρ = 0.105; p = 0.298) and argumentative ability (ρ = 0.139; p = 0.166). These findings suggest that, in this sample, attitudes toward AI are not statistically significantly related to the development of critical thinking. Therefore, the need for future research including mediating variables such as AI literacy, technical knowledge and pedagogical design arises, with the aim of delving deeper into the factors that might influence the link between the two constructs. This study provides empirical evidence for the understanding of the formative role of AI in higher education. Keywords: artificial intelligence, critical thinking, university students.